การสังเคราะห์อนุภาคระดับนาโนเมตรของซิงก์ออกไซด์โดยใช้กากฝุ่นสังกะสีจากกระบวนการชุบสังกะสีแบบจุ่มร้อน - ทิพเนตร นิลผาย (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
In this work, the synthesis of nano sized zinc oxide particles by using zinc dust waste from hot-dip galvanizing process as a starting material via precipitation method was studied. The effects of various parameters such as sodium hydroxide concentration, precipitation pH, calcination temperatures and dispersant on the physical properties and photocatalytic activity of synthesized powder were investigated. It was found that sodium hydroxide concentration, precipitation pH, calcination temperatures were crucial parameters affecting on the degree of crystallinity, crystalline size, specific surface area and photocatalytic property of the synthesized zinc oxide. By using synthesis condition of 8 M sodium hydroxide, adjusting pH at 13, and calcining at 600oC for 2 h result in phase zinc oxide with crystalline size about 69 nm and specific surface area of 14.648 m2/g with perform the highest photocatalytic degradation of methyleneblue solution under UV irradiation. The addition of optimum amount of HPC which atced as a dispersant, 0.05 g per 60 ml of solution had resulted in the improvement of photocatalytic activity of synthesized ZnO compared with that of without addition of HPC. But the photocatalytic activity of ZnO was decreased by adding with PVP. It can be suggested that the efficiency of photocatalytic activity of zinc oxide was affected by the combination factors such as the degree of crystallinity, particle dispersion, specific surface area, which could be controlled these properties by varying synthesis parameters.